EFFECTIVE TECHNOLOGY OF BIOLOGICAL TREATMENT OF HIGH CONCENTRATED WASTEWATER - Саблій, Л. А. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2013)
It is presented the results of plant researches of anaerobic-aerobic wastewater treatment with high contaminants of organic matter with using the fibrous carrier for microorganisms immobilization. In the using proposed technology it can achieved high oxidation capacity of bioreactors in COD, g/(m3∙day), with decrease at degree of wastewater treatment in the system of anaerobic-aerobic bioreactors: in anaerobic І and ІІ, respectively, – 6200 and 3400; in anoxidic І and ІІ, respectively, – 800 and 400; aerobic – 100; at concentrations of immobilized biomass on carriers, г/дм3, in anaerobic conditions – 20-30, anoxidic – to 15 and aerobic – to 6. On pilot plant establishment it was obtained the high results of wastewater treatment: effect on COD - 96-98,8%, on suspended solids - 98,5-99%, on ammonium nitrogen - 98-100%; the concentrations in treated water: COD - 19-66 mg/dm3, ammonium nitrogen - 0-0,49 mg/dm3, nitrites - 0,03 mg/dm3, nitrates - 15,8 mg/dm3, respond to norms. In the results of eating biomass bacterial part by hydrobionts of high trofical levels of bioreactors biocenose it is provided reduction of biomass amount, increasing its mineralization (over 50%) and reduction of wastes treatment costs.